Biodefense : - Bronze, Michael S. (Horizon Bioscience, 2005)
"...This book is an encyclopedic source of valid data that should not be lacking from the book collections of hospitals, general practitioners, and all others with a professional (or national defense) interest in infectious diseases and their complications."